Analisis Literatur Literasi Matematika Peserta Didik Sekolah Dasar melalui Pemecahan Masalah dalam Soal Cerita - Diana Yulius; Melva Zainil (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study intends to examine the mathematical literacy skills of elementary school students in solving story problems. The ability to read mathematics includes not only understanding concepts, but also the ability to interpret, reason, and apply mathematics in everyday situations. The focus of this study is useful for evaluating the level of literacy competence of elementary school students. The method used in this study is Literature Review (LR), without direct observation in the field. Data were obtained through the analysis of various literature sources as well as the results of relevant previous research. The results of the study show that elementary school students still face challenges in understanding information in story problems, choosing the right solution strategies, and drawing conclusions from the problems faced. These findings highlight the need for a learning approach that is more focused on developing critical thinking competencies and contextual problem-solving. Learning that prioritizes real context, group discussions, and an emphasis on critical thinking processes is needed to support students in expanding their mathematical literacy skills to the fullest.